Pedagohiya de Bista - Acuña, Tilde (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
“Pedagohiya de Bista: Mga Paglalarawan sa Pagsasalarawan” (Pedagogia de Vista: Descriptions of Illustrations) captions select images referenced in the author’s unpublished graduate thesis. These details, sans corresponding visuals, prompt the reader to reimagine each larawan (figure) and its respective aralin (lesson) and cognitively reconstruct the pages being described. Literary in form and academic in content, this essay is a hybrid work just like its subject matter: komiks.